Aspectos práticos e conceituais do modelo SWAT+ em microbacia do Olaria e Cambaí no município de Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Due to increasing industrialization and population growth, there is a need to take care of natural resources and avoid negative environmental impacts. As we know, water is a locally finite resource, hence the need for means to keep it protected and clean from human action. Thus arises the interest in hydrological models, whose characteristic is the study of water dynamics in watersheds, contributing to the realization of environmental impact simulations according to land use and occupation. This paper aims to analyze concepts and algorithms of the Soil and Water Assessment Tool (SWAT +), which is characterized by the modeling of the physical phenomena of the basin. There is also a need to understand how to get and prepare the regional input data needed to generate model results. In particular, this work analyzes the creation of the drainage network using an auxiliary tool called QSWAT within Qgis. Climate data from the basin will also be used to apply the surface runoff calculation methodology used in the model. This study will serve as a basis for the implementation of the SWAT + model, in the Cambaí and Olaria basins, in the municipality of Itaqui / RS.
Keywords: Bacia hidrográfica; SWAT+; Vazão; Watershed; Flow rate; CNPQ::CIENCIAS EXATAS E DA TERRA